Biosynthesis of alternan-stabilized selenium nanoparticles: A study on characterization and applications for antibacterial and antifungal purposes - ElObeid, Tahra; Yilmaz, Mustafa Tahsin; Ispirli, Humeyra; Sagdic, Osman; Taylan, Osman; Basahel, Abdulrahman; Karaboga, Dervis; Durak, Muhammed Zeki; Dertli, Enes (TAYLOR & FRANCIS INC, 2025)
In this study, the alternan/selenium nanoparticles (Alt/SeNPs) were characterized with respect to their formation, morphology, size, selenium distribution, molecular, crystallographic, and thermal properties using UV-Vis spectroscopy, SEM, TEM, EDAX, FTIR, XRD, DSC and TGA measurements. UV-VIS measurements confirmed the synthesis of nanoparticles by observing a maximum surface plasmon resonance peak at 212 nm. In this study, alternan contributed to stabilizing the dispersion of SeNPs, resulting in a cluster of spherical and well-dispersed nanoparticles ranging in size from 50 to 90 nanometers. Nanoparticles were found to be highly thermally stable and in a nanocrystalline structure. The ABTS and CUPRAC radical scavenging activities of Alt/SeNPs were remarkable (95% and 78% at 4 and 6 mg/mL levels of Alt/SeNPs, respectively). Alt/SeNPs had also good inhibitory activities (3.5-4.0 and 4-15 mm of inhibition zone levels at 5 mg/mL level of Alt/against foodborne pathogenic bacteria and fungi, respectively).
Keywords: Alternan-selenium nanoparticles; characterization; antioxidant and antimicrobial activities; food safety; ANTIOXIDANT ACTIVITY; ANTIMICROBIAL ACTIVITY; SILVER NANOPARTICLES; STRUCTURAL-CHARACTERIZATION; GOLD NANOPARTICLES; ELEMENTAL SELENIUM; NANO-SE; POLYSACCHARIDE; EXOPOLYSACCHARIDE; GLUCAN; Chemistry; Science & Technology - Other Topics